A graphene‐based tunable miniaturized‐element frequency selective surface in terahertz band and its application in high‐isolation multiple‐input multiple‐output system. Issue 12 (6th August 2019) - Luo, Yanbin; Zeng, Qingsheng; Yan, Xin; Hu, Nan; Xie, Wenqing; Wu, Yong; Lu, Qichao; Zhang, Xia
Abstract: Graphene is a promising material for terahertz (THz) reconfigurable devices due to the tunability of the surface conductivity. Here, a graphene‐based THz miniaturized‐element tunable band‐stop frequency selective surface (FSS) is demonstrated. The proposed FSS unit cell consists of convoluted metallic strips with graphene embedded between adjacent metallic strips. The center resonance frequency of the stop band shows an obvious blue shift from 1.76 to 2.56 THz when increasing the chemical potential of the graphene from 0 to 0.5 eV. Particularly, the convoluted design leads to an ultra‐small cell dimension of 11.73% of the free space wavelength at resonance frequency (1.76 THz). In addition, the positive role of the proposed FSS in enhancing the isolation of the multiple‐input multiple‐output (MIMO) system has been verified through two simple models. This work provides an effective method to design miniaturized‐element graphene‐based tunable FSSs, and gives a simple way to realize high‐isolation MIMO systems.